(untitled) (Research, Society and Development, 2023)
Biotechnology enables numerous processes, such as fermentation, which uses desirable microorganisms to add value to commercial importance products. Alcoholic fermentation, a type of chemical reaction carried out by microorganisms (yeasts) in sugars, yields ethanol and carbon dioxide. Fermented acetic acid has been defined as the product obtained from the acetic fermentation of alcoholic liquid from fruit must, cereal, vegetable, honey, mixtures of vegetables, and hydroalcoholic mixtures. This review aimed to introduce alcoholic and acetic fermentation concepts and highlight the importance of several research types in the fermentation of different raw materials.